STRATEGI MEWUJUDKAN PASAR NIAGA DAYA MENJADI PASAR ISLAMI BERBASIS FAST (FATHONAH, AMANAH, SIDDIQ, TABLIQ) DI DAYA KOTA MAKASSAR - Nirwana, Saina; Rahim, Rahman (Jurnal Ar-Ribh, 2020)
This study aims to determine the strategy of realizing the Daya Commercial Market into a FAST-Based Islamic Market (Fathonah, Amanah, Siddiq, Tabliq) in Makassar City Power and knowing the benefits of Islamic trade for traders in the Niaga Daya Market. This type of research used in this study is field research that produces descriptive data in the form of written data or informants and observable behavior. While the data analysis techniques used in this study were interviews, observation, and documentation. Then processed using qualitative descriptive. Based on the results of the study it can be concluded that realizing Islamic trade based on FAST, namely Fathonah (creative and smart), Amanah (trust), Siddiq (honest or transparency), Tabliq (Mutual respect), namely by creating programs that can foster awareness of traders, especially awareness will instill the nature of FAST (Fathonah Amanah Siddiq Tabliq) by forming IPPS (Sharia Market Traders Association). The benefits of Islamic trade for traders in the Niaga Daya Market are that people will be interested in shopping at the Niaga Daya market, traders can compete healthily, establish good relations between fellow traders, between traders and market managers, and between traders and buyers. In addition, traders in the Commercial Market Market can benefit both worldly and the hereafter.